2021
DOI: 10.1177/19322968211004171
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Management of Continuous Subcutaneous Basal Insulin Administration and HbA1C

Abstract: Background: While we expect that patients who adjust their insulin delivery algorithms between clinic visits to have better glucose control compared to those who do not, this effect has not been quantified. Method: This is a single-center retrospective cohort study including pediatric and adult patients with type 1 diabetes evaluating insulin pump self-management behaviors. Basal insulin dose information was obtained from the Glooko-Diasend database, and used to quantify the frequency and magnitude of basal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
(6 reference statements)
1
6
0
Order By: Relevance
“…In our questionnaire‐based study, focusing on long‐lasting insulin delivery adjustment in both bolus calculator and basal rate settings, we found a clear association between user‐driven adjustments and lower HbA1c. Taken together, ours and others’ 19 results suggest that interventions aimed at educating and empowering users in adjusting insulin pump settings could add to improved glycaemic control. However, before designing interventions, it would be relevant to investigate more closely the characteristics of those users who take responsibility for insulin pump settings adjustments, as well as the ones who never adjust settings.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…In our questionnaire‐based study, focusing on long‐lasting insulin delivery adjustment in both bolus calculator and basal rate settings, we found a clear association between user‐driven adjustments and lower HbA1c. Taken together, ours and others’ 19 results suggest that interventions aimed at educating and empowering users in adjusting insulin pump settings could add to improved glycaemic control. However, before designing interventions, it would be relevant to investigate more closely the characteristics of those users who take responsibility for insulin pump settings adjustments, as well as the ones who never adjust settings.…”
Section: Discussionsupporting
confidence: 66%
“…No distinction was made between temporary basal, suspensions and long‐lasting basal profile changes, and only individuals who adhered to certain treatment recommendations and uploaded regularly were included. The authors found frequent basal rate changes by the pump users or the parents to be associated with significantly lower HbA1c in the paediatric population, but this was not the case in the adult group 19 . In our questionnaire‐based study, focusing on long‐lasting insulin delivery adjustment in both bolus calculator and basal rate settings, we found a clear association between user‐driven adjustments and lower HbA1c.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations